Mathematical Creative Thinking Ability of the Seventh Grade Students in Terms of Learning Styles to the Preview-Question-Read-Reflect-Recite-Review (PQ4R) Learning - Istiqomah, Fiatun; Rochmad, Rochmad; Mulyono, Mulyono (Department of Mathematics, Universitas Negeri Semarang, 2017)
The purpose of this study are: (1) to know the effectiveness of PQ4R learning model in improving the creative thinking skills of the learners; (2) to know the classifications of the learners based on the levels of creative thinking skills; and (3) to describe the misconception which hampers the creative thinking skills at low level in from the learning styles of the learners. The population in this study is the seventh grade students of SMP N 21 Semarang. The method in this study is mixed method research. Quantitative data analysis uses t-test, z-test, and normalized gain test. Analysis of qualitative data using data reduction stages, data presentation, and conclusions. The results show: (1) PQ4R learning model is effective in improving the creative thinking ability of the learners; (2) the classifications of the learners based on the levels of creative thinking ability which have variations the are many of the learners who are different in each level; and (3) misconception which hampers the creative thinking skills at low level with the learning styles: (a) visual meets four misconception indicators, (b) auditorial meets three misconception indicators, and (c) kinesthetic meets six misconception indicators.